Effects of different heat treatments on Maillard reaction products and volatile substances of camel milk - Zhao, Xiaoxuan; Guo, Yinping; Zhang, Yumeng; Pang, Xiaoyang; Wang, Yunna; Lv, Jiaping; Zhang, Shuwen (Frontiers in Nutrition, 2023)
Camel milk has unique compositional, functional and therapeutic properties compared to cow's milk and also contains many protective proteins with anti-cancer, anti-diabetic and anti-bacterial properties. In this experiment, fresh camel milk was heat-treated at different temperatures and times, and the changes in Millard reaction products were analyzed. Meanwhile, headspace-gas chromatography-ion migration spectrometry (HS-GC-IMS), electronic nose and electronic tongue were used to analyze the changes of volatile components in camel milk after different heat treatments. The results showed that the Maillard reaction was more severe with the increase of heat treatment, and the contents of furosine and 5-hydroxymethylfurfural increased significantly when the heat treatment temperature was higher than 120°C. HS-GC-IMS results showed that the contents of aldehydes and ketones increased obviously with the increase of heat treatment degree. The study clarifies the effects of different heat treatment degrees on Maillard reaction degree and flavor of camel milk, which has practical production guidance significance for the research and industrialization of liquid camel milk products.